Five Fragments of Cicero’s Letters Ad familiares - Reeve, Michael D. (Ciceroniana On Line, 2024)
Three fragments of Cicero’s letters Ad familiares assigned in 1857 and 1867 to the 12th century or earlier have been thought to shed light on the corrections made by Salutati and Niccoli in P (the manuscript written for Salutati in 1392), and two more perhaps connected with these three have since emerged. The evidence is reappraised, and in relation to the corrections in P other strands of tradition attested in 15th-century Italy are discussed. Pending collation of manuscripts written between 1392 and Niccoli’s death in 1437, L. Mendelssohn’s view can stand: when not conjectures, the corrections in P came directly or indirectly from its exemplar, the 9th-century manuscript M.